PENERAPAN POP UP BOOK SEBAGAI MEDIA PEMBELAJARAN DALAM MENINGKATKAN PENGUASAAN MUFRODAT SISWA KELAS V MIN 2 KOTA MAKASSAR - Nurfa Sri Alfiah; Abdul Qahar Zainal; Abdul Wahab; Rosmiati; Said Syarifuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning Arabic is one of the important subjects that must be understood and mastered by students, especially for those who study in Islamic-based educational institutions. One such institution is Islamic elementary school 2 Makassar, where many students still struggle to master Arabic vocabulary. To address this issue, the researcher offers the Pop-Up Book as a learning aid. A Pop-Up Book is a type of book featuring three-dimensional visual displays that are attractive and interactive. This medium is expected to help students understand and memorize mufrodat more easily through engaging 3D visualizations. This study aims to obtain data on the implementation of the Pop-Up Book media in improving the mastery of Arabic mufrodat among fifth-grade students of class V.C at MIN 2 Makassar. This research uses a Classroom Action Research (CAR) approach. The researcher selected the students of class V.C at MIN 2 Makassar as the research subjects. The data collection techniques used were observation, tests, and documentation. The research results showed an improvement in students’ vocabulary mastery after implementing the Pop-Up Book media. The average student score in Cycle I was 78.52, with 18 students (64.28%) passing and 10 students (35.71%) not passing. In Cycle II, the average score increased to 85.71, with 24 students (85.71%) passing and 4 students (14.28%) not passing. Based on the results of the study, it can be concluded that the use of Pop-Up Book as a learning medium can improve the Arabic vocabulary mastery of fifth-grade students in class V.C at MIN 2 Makassar.